Analisis Minat Kewirausahaan Siswa Pada Materi Aritmetika Sosial - Rina Wijayanti; Dela Yuniarti; Siti Napfiah (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2026)
Mathematics learning in schools is generally still considered a challenging subject by students because it is perceived as having limited relevance to everyday life, which results in suboptimal development of students’ interest in learning and entrepreneurship. One mathematical topic that is directly related to real-life situations is social arithmetic, which includes concepts such as purchase price, selling price, profit, loss, discounts, and taxes. The main objective of this study is to explore the role of social arithmetic material as a driver of students’ entrepreneurial interest. This research employs a qualitative approach with a descriptive research design. The subjects of this study were five students from SMP Kristen 1 YPK Malang. Data were collected using questionnaires on students’ entrepreneurial interest and semi-structured interviews, and then analyzed using data reduction techniques, data display, and conclusion drawing. The findings indicate that students have a fairly good understanding of social arithmetic material, especially when learning is supported with examples relevant to everyday life. In addition, learning social arithmetic can increase students’ interest in buying and selling activities and encourage entrepreneurial interest, although there is variation in students’ levels of confidence. The conclusion of this study is that social arithmetic material functions as a driver of students’ entrepreneurial interest, particularly when presented through contextual learning methods and supported by hands-on practice activities.